“Making visible the invisible”: Exploring the role of gender biases on the glass ceiling in Qatar's public sector - Rabia Naguib (17884538) (2023)
Most studies exploring the impact of gendered organizational factors on women's leadership opportunities have focused on Western economies. This study investigates how unconscious gender bias is hindering women's access to leadership in Qatar's public sector. We conducted 45 semi-structured interviews with both male and female employees working in the Qatari public sector to understand their perceptions, attitudes, and experiences regarding women's career support, leader preferences, and work-family balance issues. Our findings reveal the existence of unconscious gender bias among male and female employees in the Qatari public sector. While many participants recognized recent efforts to promote gender equality in employment and career advancement, and felt that women face no barriers to their career advancement, they also expressed preferences for male managers over female ones. Additionally, while women faced more challenges than men in maintaining work-life balance, some male participants attributed these struggles to individual women's abilities rather than acknowledging systemic gender biases. These biases, both in the workplace and at home, underscore the underestimated and unacknowledged role of gender in contributing to the glass ceiling effect in Qatar's public sector. Other Information Published in: Women's Studies International Forum License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.wsif.2023.102723